Efektivitas dan Jaminan Hukum Sertifikat Halal Self Declare di Indonesia - Saipul Rohman; Amoury Adi Sudiro (UNES Law Review, 2023)
The issuance of Government Regulation (PP) No. 39 of 2021 concerning the Implementation of the Halal Product Guarantee Field and Minister of Religion Regulation No. 20 of 2021 concerning Halal Certification for MSEs. Self Declare independent halal application service helps businesses to obtain halal certification effectively and efficiently. But in its implementation, there are several differences in the process of issuing halal certification and legal guarantees for registered products. In this study the authors used a legal methodology system Descriptive analysis method used for specifications. The data collection techniques used are direct observation and documentary research. Data conducted through empirical juridical data analysis strengthens the validity of the research to test the effectiveness and legal security of the self-declared halal certification process.